Factors Associated with Alcohol Consumption among Adolescents in Selected Secondary Schools in a Local Government Area of Oyo State, Southwest, Nigeria - Olaniyi, Adenike A.O.; Jimoh, S.O. (International Journal of Child Health and Nutrition, 2021)
Alcohol use during adolescence and young adulthood remain a prominent public health problem. This study identifies factors associated with alcohol consumption among adolescents in selected secondary schools in Ibadan North Local Government Area, Southwest, Nigeria. A cross-sectional descriptive study was used. One hundred and seventy-six (176) respondents were consecutively selected using the random technique. Data were analyzed using chi-square and hypotheses tested at a 5% level of significance. Findings revealed that the majority of the respondents had poor knowledge of alcohol consumption, while (36.4%) of the respondents had consumed alcoholic beverages. Over half (54.5%) engaged in drinking alcohol as a result of peer influence. The majority (70%) of them had good knowledge of factors influencing alcohol consumption and factors influencing consumption among the respondents. Thus, the rate of alcohol consumption among adolescents was low (36.4%) as a larger percentage (64.6%) of them did not consume alcohol owing to their knowledge of the effect and the presence of some protective factors within the environment. In conclusion, alcohol consumption among adolescents was low, knowledge of its consumption was high, and it was associated with its actual consumption. Alcohol use is also associated with peer influence and environmental variables, while age and gender did not have any relationship with alcohol consumption. Therefore, educational intervention to improve knowledge of the consequences of alcohol consumption among adolescents and public policies with preventive educational campaigns was recommended.